Clinical trial risk in leukemia: Biomarkers and trial design. Issue 1 (28th October 2020) - Li, Alice J.; Dhanraj, Jasper P.; Lopes, Gilberto; Parker, Jayson L.
Abstract: This study analyzed the risk of clinical trial failure for leukemia drug development between January 1999 and January 2020. The specific leukemia subtypes of interest were acute lymphocytic leukemia (ALL), chronic lymphocytic leukemia (CLL), acute myeloid leukemia (AML), and chronic myeloid leukemia (CML). Drug development was investigated using data obtained from https://www.clinicaltrials.gov and other publicly available databases. Drug compounds were excluded if they began phase I testing for the indication of interest before January 1999, if they were not industry sponsored, or if they treated secondary complications of the disease. Further analysis was conducted on biomarker usage, drug mechanisms of action, and line of treatment. Drugs were identified following our inclusion criteria for ALL (72), CLL (106), AML (159), and CML (47). The likelihood (cumulative pass rate), a drug would pass all phases of clinical testing and obtain Food and Drug Administration approval, was 18% (ALL), 10% (CLL), 7% (AML), and 12% (CML). Biomarker targeted therapies improved the success rates by three‐ and sevenfold, for ALL and AML, respectively. Enzyme inhibitors doubled the cumulative success rate for AML. First‐line therapy and kinase inhibitors both independently doubled the cumulative success rate for CLL. Oncologists enrolling patients in clinical trials can increase success rates by up to sevenfold by prioritizing participation in trials involving biomarker usage, while consideration of factors such as drug mechanism of action and line of therapy can further double the clinical trial success rate.